Genetics and molecular biology of muscle adaptation (Advances in sport and exercise science series, 2006)
This book starts with the origin of life and ends with the mechanisms that make muscles adapt to different forms of training. In between, it considers how evidence has been obtained about the extent of genetic influence on human capacities, how muscles and their fibres are studied for general properties and individual differences, and how molecular biological techniques have been combined with physiological ones to produce the new discipline of molecular exercise physiology. This is the first book on such topics written specifically for modules in exercise and sport science at final year Hons BSc and taught MSc levels. Contents 1. Origins 2. Top-down studies of genetic contribution to differences in physical capacity 3. Types of skeletal muscle fibre 4. Introduction to molecular exercise physiology 5. Adaptation to endurance training 6. Adaptation to resistance training Appendix 1: Histochemical methods Appendix 2: RNA extraction and quantitative RT-PCR Appendix 3: Muscle extraction and Western blotting protocol Glossary